2007
DOI: 10.1016/j.juro.2007.05.171
|View full text |Cite
|
Sign up to set email alerts
|

Postpubertal Urodynamic and Upper Urinary Tract Changes in Children With Conservatively Treated Myelomeningocele

Abstract: This study demonstrates that total cystometric bladder capacity, maximum detrusor pressure and detrusor leak point pressure increase significantly in patients with myelomeningocele following puberty. The increase in bladder capacity could be attributed to increasing bladder outlet resistance resulting from prostate gland enlargement in males and estrogenization in females. A significant number of patients spontaneously achieve continence at puberty, and continence becomes more likely when increased total cysto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…Proposed reasons are 1) adolescent rebellion against the discipline of CIC or medication, and/or 2) increased bladder outlet resistance due to growth of the prostate and estrogenization of the female urethra, or 3) tethering of the spinal cord [30]. A study by Almodhen et al in a group of 37 patients showed that total cystometric bladder capacity, maximum detrusor pressure and detrusor leak point pressure significantly increased after puberty [31]. Symptomatic tethered cord occurs in 2.8–32% in all patients who underwent surgical myelomeningocele repair in the neonatal period [32].…”
Section: Discussionmentioning
confidence: 99%
“…Proposed reasons are 1) adolescent rebellion against the discipline of CIC or medication, and/or 2) increased bladder outlet resistance due to growth of the prostate and estrogenization of the female urethra, or 3) tethering of the spinal cord [30]. A study by Almodhen et al in a group of 37 patients showed that total cystometric bladder capacity, maximum detrusor pressure and detrusor leak point pressure significantly increased after puberty [31]. Symptomatic tethered cord occurs in 2.8–32% in all patients who underwent surgical myelomeningocele repair in the neonatal period [32].…”
Section: Discussionmentioning
confidence: 99%
“…It is important for the practitioner to consider that adolescent hormonal changes may impact the lower urinary tract. It has been shown bladder outlet resistance may increase in teenagers, the result of prostatic enlargement in boys38 and estrogenization in girls. While 45% with incontinence become continent after going through puberty, this does not result in upper urinary tract deterioration.…”
Section: Follow‐up Of Congenital Neuropathic Bladder Dysfunction In Cmentioning
confidence: 99%
“…However, patients with inadequate bladder outlet resistance are more likely to have persistent incontinence. Some evidence indicates that continence status and bladder function may change at puberty [10,11]. Almodhen et al [10] found that a signifi cant number of patients who had no prior bladder outlet surgery achieved spontaneous continence at puberty.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Some evidence indicates that continence status and bladder function may change at puberty [10,11]. Almodhen et al [10] found that a signifi cant number of patients who had no prior bladder outlet surgery achieved spontaneous continence at puberty. They documented that bladder capacity, compliance, and detrusor leak point pressure all increased after puberty.…”
Section: Clinical Presentationmentioning
confidence: 99%